1974
DOI: 10.1177/009365027400100303
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Duration of the Effect of Aggressive,, Violent, and Erotic Communications On Subsequent Aggressive Behavior

Abstract: _ This study investigated the aggression-modifying, immediate effect on provoked individuals of exposure to a neutral, an aggressive, a violent, or an erotic communication. All communications were followed by a common, noninvolving, nonaggressive communication. Under these conditions, neither the effect of the aggressive nor that of the violent communication differed appreciably from the effect of the neutral communication. In contrast, the effect of the erotic communication significantly exceeded the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…Failure to yield a more robust effect in the physiology data could likely be attributed to the use of events that failed to generate sufficient arousal to benefit subsequent stimuli. Zillmann et al (1974) noted that the magnitude and duration of transfer effects is dependent upon the arousalinducing properties of the initial stimulus, and they concluded that erotica is particularly adept at facilitating this effect. The stimuli used here were likely mundane by comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to yield a more robust effect in the physiology data could likely be attributed to the use of events that failed to generate sufficient arousal to benefit subsequent stimuli. Zillmann et al (1974) noted that the magnitude and duration of transfer effects is dependent upon the arousalinducing properties of the initial stimulus, and they concluded that erotica is particularly adept at facilitating this effect. The stimuli used here were likely mundane by comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Although decay rates are not absolute (Mattes & Cantor, 1982;Zillmann, Hoyt, & Day, 1974), the excitatory component of emotional response is slow to dissipate (Zillmann, 1996a). Residual arousal from an initial stimulus acts in an additive fashion to intensify arousal generated by a subsequent stimulus, provided that the individual does not have obtrusive cues linking that residual arousal to the prior event.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results are consistent with what we know about the short-term effects of thoughts, feelings, and arousal. For instance, state hostility is an emotion, which is defined as short lived [Larson, 2000]; aggressive thoughts should dissipate once primed as soon as other thoughts, memories, or knowledge structures get primed (an idea similar to masking in the perception literature); and research has shown that physiological arousal after exposure to violent stimuli lasts longer than 5 min [Zillmann et al, 1974]. However, we are unaware of any literature that has attempted to determine how long the probability of using aggressive behavior lasts after violent media exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Arousal and aggressive behavior, on the other hand, may not dissipate immediately. Evidence has shown that more than 5 min is necessary to reduce arousal after exposure to violent stimuli to baseline [Zillmann et al, 1974], while it is unknown how long aggressive behavioral tendencies will last. …”
Section: Introductionmentioning
confidence: 99%
“…The brief time course of emotional experience yields correspondingly fleeting effects on behaviours, judgements, and memory. Anger, for example, loses its potency after only minutes (Zillman, Hoyt & Day, 1974). Episodic memory for experienced emotion seems to last only for a matter of days (Robinson & Clore, 2002), and emotion is the most readily forgotten detail in autobiographical memory (Odegard & Lampinen, 2004).…”
Section: Emotional Inhibition In Autobiographical Memorymentioning
confidence: 99%